Details of Writing Scientific Journal Articles: An Editor’s Perspective - JIANG Xia, LI Canbing (Shanghai Jiaotong Daxue xuebao)
Academic writing is a time-consuming process that requires authors to possess specific writing skills, as well as a thorough understanding of format standards and publishing ethics of scientific journals. This paper analyzes the submission process for special columns in Journal of Shanghai Jiao Tong University, aiming to address basic considerations that novice authors should keep in mind in the early stages of academic writing. The goal is to help these authors submit manuscripts that are logically structured and meet the academic standards of their target journals. This paper is unique in its focus on common issues encountered in submissions, providing practical advice through a point-by-point analysis. By incorporating easy-to-understand cases, it provides a helpful reference for novice researchers seeking to navigate the requirements and pitfalls of writing for scientific journals.